Right time to use pioneering structural studies on β-lactam related enzymes - Rabe, P; McDonough, M; Schofield, C (RXNet, 2019)
Standfirst: Following from the ‘golden age’ of antibacterials, how have biophysical analyses on the enzymes targeted by penicillins together with those responsible for resistance and biosynthesis aided in antibiotic drug discovery as well as providing unexpected insights into human biochemistry? Read on below.